A SELECTION OF METHODS AND TECHNIQUES PROFESSIONAL TEACHERS CAN APPLY TO THEIR OWN LIFELONG LEARNING - Kusnere, Ilga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
A selection of methods and techniques professional teachers can apply to their own lifelong learning.Education is the key to converting knowledge and experience into practical actions, their analysis and application. It plays a key role in the synthesis of new knowledge into research and innovation. Such thoughts on education were expressed in the resolution of the sixth World Education Congress in 2011. Today, when world education forums are widely discussing how schools can better organise the learning process, when ambitious long-term reforms are being implemented in the Latvian education system—the transition to competency-based educational content and teaching methods—it is essential to assess current situation and to bring innovative methods and techniques to our teachers' own learning process. The new knowledge and experience teachers gain through lifelong learning, through their experience and the understanding of how to share it, can be presented and guided by such methods and techniques that enrich a teacher's emotional and intellectual function. My own research has confirmed my belief that for a teacher to be confident and capable enough to help her students discover the joy of learning and gain new knowledge through the process of education, that teacher must herself have the experience of active learning, insight, and personal growth through the learning process.The author has selected a number of methods and techniques for lifelong learning based on the methods and techniques developed by a number of education researchers (Kolb, 1984; Koķe, 1999; Stueck, 2010; Vedins, 2011; Ščurkova, 2016; Robinson, 2013; Amonašvili, 2017), and on her own experience of leading and developing a professional lifelong education programme for teachers. The model of teacher learning presented here has been used in practice since 2012 and has been well-received. Teachers can develop themselves mentally, emotionally and spiritually through the learning process and in doing so increase their professional value.Objective for the Study. To create a model for teaching professional teachers in the context of their own lifelong learning, to assemble a selection of methods and techniques for professional teachers’ lifelong learning, including several designed by the author, and to assess them.